Color Stability of Milled Versus Printed High-Density Polymers Provisional Restorations - Baroom, Omar. (Tufts University. Tisch Library., 2023)
Thesis (M.S.)--Tufts University, 2023.; Submitted to the Dept. of Posthodontics.; Advisor: Ali Muftu.; Committee: Aikaterini Papathanasiou, Maria Avrampou, and Sarah Pagni.; Keyword: Dentistry.